Penggunaan Media Papan Pintar Untuk Meningkatkan Kemampuan Numerasi Anak Usia Dini Dalam Mengenal Lambang Bilangan 1-5 - Imas Basmiati; Tanto Aljauharie Tantowie; Desi Suryani (Bildung: Jurnal Ilmu Pendidikan, 2025)
This study aims to improve early childhood numeracy skills in recognizing number symbols 1-5 using smart board media. The research method used is Classroom Action Research (CAR) carried out in two cycles. The subjects of the study were children aged 4-5 years at PAUD Kober Assulha, totaling 14 children. Data were collected through observation and numeracy ability tests. The results of the study showed that the smart board was effective in enhancing children's understanding of number symbols 1-5. Children who reached the "Developing as Expected" (DAE) category were 7%, "Developing Very Well" (DVW) reached 2%, "Starting to Develop" (SD) was 24%, and "Not Yet Developing" was 67%. These results confirm that the smart board can facilitate effective numeracy learning. Continuous evaluation and intervention are necessary to maintain and enhance the learning outcomes that have been achieved. Research results indicate that the use of smart board media is significantly expected to improve children's ability to recognize number symbols 1-5. This improvement is evident from the class average scores and the active participation of children in learning activities.